Removal of Citric Acid by Activated Carbon Adsorption - Inci, Ismail (Asian Journal of Chemistry, 2016)
The possibilities of removal of citric acid using activated carbon have been investigated. During the analysis initial citric acid concentration and amount of activated carbon have been taken into account. The experiments were conducted with aqueous solutions containing citric acid in four different concentrations (4, 4.5, 7, 13%, w/w). As adsorbent activated carbon was used in five different amount (0.005, 0.010, 0.015, 0.020, 0.025 g). Considerable amount of citric acid was removed by activated carbon. The amount of acid removed by activated carbon depends upon activated carbon amount. Experimental data were fitted into the Freundlich isotherm to obtain the values of adsorption parameters.